THE EFFECT OF PEER REVIEW STRATEGY ON THE STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE PARAGRAPH - Sri Agus Murniasih; I Wayan Dirgeyasa (Universitas Negeri Medan, 2015)
This study was conducted to know the effect of applying Peer Review Strategy on the students’ achievement in writing descriptive paragraph. It was conducted by using experimental research method. This research design was conducted pre-test, post test in experimental and control group. The population of this research was the eight (VIII) grade students of SMP IT IQRA’ Medan. The sample of this research was taken by lottery technique. They were in class VIII-1 by experimental group and the class VIII-2 by control group. The experimental group was taught by using Peer Review Strategy while the control group was given no treatment. The instrument used to collect the data was writing essay test. The data were analyzed by using t-test formula. The result showed that the value of t-observed was higher than the value of t-table. (3,55 > 2,05 (a = 0.05)) with the degree of freedom (df) = 28. It means that there was a significant effect of applying Peer Review Strategy on the students’ achievement in writing descriptive paragraph. So, the alternative hypothesis (Ha) was accepted.